Factors affecting deer pressure on forest regeneration: The roles of forest roads, visibility and forage availability. Issue 2 (16th December 2020) - Borowski, Zbigniew; Bartoń, Kamil; Gil, Wojciech; Wójcicki, Adam; Pawlak, Bogdan
Abstract: BACKGROUND: Deer pressure on forest regeneration constitutes a serious problem in commercial forests in the northern hemisphere due to the increase in deer populations. However, other drivers, such as climate, landscape structure and the level of human activity, have a strong influence on deer pressure. The direct, density‐related impacts of ungulates on forest regeneration have been well studied, but there is limited empirical evidence related to the indirect factors mentioned above. We conducted a field experiment in three forest divisions in Poland to evaluate the role of a common element of human infrastructure, i.e. small, unpaved forestry roads. Additionally, we assessed the modifying effect of visibility driven by vegetation cover and forage availability. RESULTS: The proximity of unpaved roads affected deer habitat use and foraging behaviour, and limited browsing pressure on regenerating forests. Low visibility and higher winter forage availability increased the probability of tree browsing. We observed different responses to roads in two deer species: red deer avoided roads, while roe deer browsed in the vicinity of roads. CONCLUSIONS: A typical forest network of unpaved roads creates a landscape of fear for red and roe deer, and limits browsing pressure on regenerating forests due to the changes in deer habitat use, activity patterns and foraging behaviour. Knowledge of the factors influencing browsing pressure can help to spatially optimise the application of protective measures for tree seedlings. Abstract : We observed different responses to forest roads in two deer species: red deer avoided roads, while roe deer browsed tree seedlings in the vicinity of roads. © 2020 Society of Chemical Industry